EU emissions trading: Distinctive behavior of small companies - Helene Naegele; Aleksandar Zaklan (DIW Economic Bulletin, 2016)
The EU Emissions Trading System (EU ETS) is the cornerstone of the European Union's climate policy and covers just under half of the EU's greenhouse gas emissions. More than ten years since the EU ETS was first introduced, there continues to be substantial research interest regarding its functioning and the behavior of participating companies. DIW Berlin conducted three econometric studies based on microdata at company and/or installation level. The findings suggest that, overall, there are only minor distortions in the behavior of companies regulated by the EU ETS. However, the studies also show that small companies exhibit distinctive behavior which could result in inefficiencies. For instance, during Trading Phase I, small companies participated less actively in trading allowances than companies with a higher turnover. Moreover, the emissions produced by small power plants depend, to a certain extent, on the allocation rules. Small companies also often fail to take full advantage of the cost reduction potential of international offset credits: for a total of 22 percent of all companies (predominantly small emitters), an average of 31,000 euros in cost reduction potential remained unused. The barriers causing this loss may be interpreted as fixed transaction costs. For further ex-post analyses, the timely provision of user-friendly emissions trading data at the installation level would be very beneficial.
Keywords: Q54; Q58; D23; 330; emissions trading; EU ETS; transactions cost; offsets; participation